Discrimination of cirrhotic nodules, dysplastic lesions and hepatocellular carcinoma by their vibrational signature. Issue 1 (December 2016) - Peng, Chengyuan; Kaščáková, Slávka; Chiappini, Franck; Olaya, Natalia; Sandt, Christophe; Yousef, Ibraheem; Samuel, Didier; Dumas, Paul; Guettier, Catherine; Naour, François
Abstract Background Hepatocarcinogenesis is a multistep process characterized in patients with chronic liver diseases by a spectrum of hepatic nodules that mark the progression from regenerative nodules to dysplastic lesions followed by hepatocellular carcinoma (HCC). The differential diagnosis between precancerous dysplastic nodules and early HCC still represents a challenge for both radiologists and pathologists. We addressed the potential of Fourier transform-infrared (FTIR) microspectroscopy for grading cirrhotic nodules on frozen tissue sections. Methods The study was focused on 39 surgical specimens including normal livers (n = 11), dysplastic nodules (n = 6), early HCC (n = 1), progressed HCC on alcoholic cirrhosis (n = 10) or hepatitis C virus cirrhosis (n = 11). The use of the bright infrared source emitted by the synchrotron radiation allowed investigating the biochemical composition at the cellular level. Chemical mapping on whole tissue sections was further performed using a FTIR microscope equipped with a laboratory-based infrared source. The variance was addressed by principal component analysis. Results Profound alterations of the biochemical composition of the pathological liver were demonstrated by FTIR microspectroscopy. Indeed, dramatic changes were observed in lipids, proteins and sugars highlighting the metabolic reprogramming in carcinogenesis. Quantifiable spectral markers were characterized by calculating ratios of areas under specific bands along the infrared spectrum. These markers allowed the discrimination of cirrhotic nodules, dysplastic lesions and HCC. Finally, the spectral markers can be measured using a laboratory FTIR microscope that may be easily implemented at the hospital. Conclusion Metabolic reprogramming in liver carcinogenesis can constitute a signature easily detectable using FTIR microspectroscopy for the diagnosis of precancerous and cancerous lesions.